2006
DOI: 10.1289/ehp.8619
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Stress Axis and Neurochemical Alterations in Specific Brain Areas by Concentrated Ambient Particle Exposure with Concomitant Allergic Airway Disease

Abstract: ObjectiveExposure to ambient particulate matter (PM) has been linked to respiratory diseases in people living in urban communities. The mechanism by which PM produces these diseases is not clear. We hypothesized that PM could act on the brain directly to stimulate the stress axis and predispose individuals to these diseases. The purpose of this study was to test if exposure to PM can affect brain areas involved in the regulation of neuroendocrine functions, especially the stress axis, and to study whether the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(50 citation statements)
references
References 61 publications
2
47
0
1
Order By: Relevance
“…Adrenaline concentrations, on the other hand, decreased. Growing DA and/or NA concentrations in the brain of animals subjected to stress is a reaction which has been observed by many authors [9,10,22]. In stressed animals, like in our study, a significant reduction of the DOPAC/DA and and mesencephalon of both BAC-exposed groups relative to control.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Adrenaline concentrations, on the other hand, decreased. Growing DA and/or NA concentrations in the brain of animals subjected to stress is a reaction which has been observed by many authors [9,10,22]. In stressed animals, like in our study, a significant reduction of the DOPAC/DA and and mesencephalon of both BAC-exposed groups relative to control.…”
Section: Resultssupporting
confidence: 87%
“…Glucocorticoids are important in the maintenance of functional and structural integrity of the brain. Therefore, increased blood glycocorticoid concentrations cause changes in the functional condition of the neurotransmission systems, and of the catecholaminergic systems in particular [8][9][10]. Data assessing BAC effects on central nervous system of experimental animals in inhalation exposure situations could not be located in the accessible literature.…”
Section: Biological Materials Collectionmentioning
confidence: 99%
“…It has become apparent that inhalation of particulate matter (PM) can have influence on the CNS. Recent work with experimental animals has provided evidence for neuropathological effects, including reduced dopaminergic neuron density in mice exposed to concentrated ambient particles (CAPs) [22], and changes in neurotransmitter levels in rats exposed by inhalation to CAPs [23]. There is some evidence from animal studies that inhaled particles, especially the ultrafine size fraction, may be able to distribute to the brain [24][25][26].…”
Section: Depression Casesmentioning
confidence: 99%
“…Previous studies indicated an association between chemical exposure in the environment and monoaminergic neurotransmitter regulation (Matsuda et al, 2010;Xia et al, 2011;Sirivelu et al, 2006). The monoaminergic system plays an important role in mental health, and its dysregulation leads to psychiatric dysfunction, such as behavioral depression, anxiety disorder, and Parkinsonism (Weiss et al, 1981;Elsworth and Roth, 1997;Morilak and Frazer, 2004).…”
Section: Discussionmentioning
confidence: 99%